Capitals controls and macroprudential measures: What are they good for? - Kristin Forbes; Marcel Fratzschner; Roland Straub (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Are capital controls and macroprudential measures successful in achieving their objectives? Assessing their effectiveness is complicated by selection bias and endogeneity; countries which change their capital-flow management measures (CFMs) often share specific characteristics and are responding to changes in variables that the CFMs are intended to influence. This paper addresses these challenges by using a propensity-score matching methodology. We also create a new database with detailed information on weekly changes in controls on capital inflows, capital outflows, and macroprudential measures from 2009 to 2011 for 60 countries. Results show that macroprudential measures can significantly reduce some measures of financial fragility. Most CFMs do not significantly affect other key targets, however, such as exchange rates, capital flows, interest-rate differentials, inflation, equity indices, and different volatilities. One exception is that removing controls on capital outflows may reduce real exchange rate appreciation. Therefore, certain CFMs can be effective in accomplishing specific goals-but most popular measures are not good for accomplishing their stated aims.
Keywords: F3; F4; F5; G0; G1; 330; capital controls; macroprudential measures; propensity-score matching; selection bias; capital flows; emerging markets